2006
DOI: 10.1055/s-2006-946683
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Macrocyclic Diterpenoid Esters from Euphorbia cornigera

Abstract: Root extract of Euphorbia cornigera Boiss. (Euphorbiaceae) was separated into seven (compound 1-7) isolates through multiple Craig's distributions and preparative HPLC. The structures and relative configuration of theses compounds were established via spectral analyses as 7,8,12- O-triacetyl-3- O-(2-methylbutanoyl)-ingol (1), 3,8,12- O-triacetyl-7- O-(2-methylbutanoyl = -ingol (2), 3,7,12- O-triacetyl-8- O-(2-methylbutanoyl)-ingol (3), 3,7,8- O-triacetyl-12- O-(2-methylbutanoyl)-ingol (4), 7,12- O-diacetyl-3- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 12 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…Fortunately, Euphorbiaceae family, which is one of the largest families of plants, comprising 300 genera and 7500 species, is commonly available in plain, mountainous, and desert areas of Pakistan [10,11]. These plants are popular among the local people for the treatment of various ailments including cancer [11 -13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, Euphorbiaceae family, which is one of the largest families of plants, comprising 300 genera and 7500 species, is commonly available in plain, mountainous, and desert areas of Pakistan [10,11]. These plants are popular among the local people for the treatment of various ailments including cancer [11 -13].…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxicity assay of samples 1-4 was evaluated on RAW and HT-29 cell lines, using the MTT assay as described previously [9,10]. The amrubicin hydrochloride salt was used as a control and all the measurements were taken in triplicate.…”
mentioning
confidence: 99%
“…The active portion of the material was identified by testing against mouse ear. The selected crude was subjected to HPLC to get pure compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these aspects prompted us to investigate its biologically active constituents. In previous studies, we reported biologically active compounds from the latex [8,9]. In the present investigation, 10 compounds (1-10) were isolated and their structures were elucidated (Figure 1), and their biological activity was assessed.…”
Section: Introductionmentioning
confidence: 83%
“…[1][2][3] The most famous are cembranes, jatrophanes, lathyranes; on the contrary, casbanes and dolabellanes are rather rare in nature. [1,[3][4][5][6][7] Their carbohydrogen skeleton is 14-, 12, or 11-membered cycle fused with cyclopropane, cyclopentane [1,3,6] or oxirane [7] rings. It should be emphasized that each naturally occurring macrocyclic diterpenoid is a one molecule (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%